Our others : stories of Ukrainian diversity - I͡Aremchuk, Olesi͡a (Ukrainian voices (Stuttgart, Germany), 2020)
"Our Others: Stories of Ukrainian Diversity is an award-winning exploration of both the histories and personal stories of fourteen ethnic minority groups living within the boundaries of present-day Ukraine: Czechs and Slovaks, Meskhetian Turks, Swedes, Romanians, Hungarians, Roma, Jews, 'Liptaks', Gagauzes, Germans, Vlachs, Poles, Crimean Tatars, and Armenians. Based on a combination of academic research, fieldwork, and interviews, Olesya Yaremchuk's literary reportages paint realistic, thoughtful, and historically informed depictions of how these various groups arrived in Ukraine and how they have fared within the country's borders. Accompanied by vivid photographs that bring the reportages to life, Our Others is in some respects a chronicle of the myriad voluntary and forced migrations that have rolled through Ukraine for centuries. Simultaneously, the book offers a tender--and timely--study of the little islands of cultural diversity in Ukraine that have survived the Soviet steamroller of planned linguistic, cultural, and religious unification and that deserve acknowledgement in Ukraine's broader cultural identity."--